The Influence of Money Ethics, Love of Money, Materialism, and Religiosity on Tax Avoidance with Financial Conditions as Moderating Variables: Pengaruh Etika Uang, Cinta Uang, Materialisme, dan Religiusistas Terhadap Penghindaran Pajak dengan Kondisi Keuangan Sebagai Variabel Moderasi - Hadian, Bagas Jihad; Ernandi, Herman (Indonesian Journal of Innovation Studies, 2022)
Taxes are one of the most important factors in carrying out national development, tax revenues reach approximately 70% of all state revenues. As a good citizen, you must pay taxes. This study aims to examine the effect of money ethics, love of money, materialism, and religiosity on tax evasion with financial conditions as moderating variables. In this study using quantitative techniques through smart PLS data processing tools, data was taken by primary data or questionnaires then sampling based on the census was used as the research sample. In accordance with the results of the study, it was found that religiosity had an effect on tax evasion with financial condition as a moderating variable, materialism had an effect on tax evasion with financial condition as a moderating variable, Love of Money had an effect on tax evasion with financial condition as a moderating variable, Money Ethics had an effect on tax evasion with financial condition as a moderating variable.